Cost-Effectiveness Analysis of Immunosuppressant Drug Methylprednisolone at Gembleb Farma Trenggalek Pharmacy Service - Fendy Prasetyawan; Yuneka Saristiana; Tsamrotul Ilmi; Widhi Astutik; Chandra Arifin; Abd Rofiq; Eka Hayati Rhomah (International Journal of Science and Society (IJSS), 2025)
This study aims to evaluate the cost-effectiveness of the immunosuppressant drug methylprednisolone at Gembleb Farma Pharmacy in Trenggalek, East Java, Indonesia. The research was conducted on May 30, 2025, using a descriptive quantitative approach supported by interviews with the responsible pharmacist. Data collection involved daily sales records of methylprednisolone and clinical response outcomes among patients. Each patient typically received five tablets per treatment, and the pharmacy recorded an average daily sale of 250 tablets. Therefore, it was estimated that approximately 50 patients were served per day. From those, 45 patients—equivalent to 90%—experienced favorable clinical responses to methylprednisolone therapy. The cost per tablet was IDR 500, resulting in a total daily cost of IDR 125,000. The calculated Cost-Effectiveness Ratio (CER) per day was IDR 2,777.78 per effectively treated patient. This value remained consistent when scaled to monthly (IDR 3,750,000 for 1,350 effective patients) and annual estimates (IDR 45,625,000 for 16,425 effective patients), yielding the same CER value of IDR 2,777.78. The findings indicate that methylprednisolone provides a stable and predictable cost-effectiveness profile in outpatient pharmacy settings. These results may support decision-making in therapeutic planning, particularly in community pharmacies that aim to deliver effective yet affordable immunosuppressive therapies. Additionally, this cost-efficiency aligns with the goals of rational drug use and sustainable pharmaceutical services at the primary healthcare level.